2011
DOI: 10.1007/s00044-011-9655-8
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and docking studies of novel ofloxacin analogues as antimicrobial agents

Abstract: A number of novel ofloxacin analogues were synthesized by modifying the carboxylic acid at C-6. To investigate the antimicrobial data on structural basis, in-silico docking studies of the tested compounds into the crystal structure of topoisomerase II using Autodock vina 4.0 program was performed in order to predict the affinity and orientation of the synthesized compounds at the activities. R 2 values show good agreement with predicted binding affinities obtained by molecular docking studies. Also, it is veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Antibiotic resistance is becoming a serious threat to public health and there is an urgent need for new and improved antimicrobial agents [1][2][3][4][5]. The occurrence of 1,2,4-triazole system in numerous biologically active molecules has been recognized to possess activities, such as analgesic [6], antibacterial [7][8][9], antifungal [10,11], anti-inflammatory [12], antitumor [13,14], antitrypanosomal [15], antiproliferative [16] and antibiotics properties [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is becoming a serious threat to public health and there is an urgent need for new and improved antimicrobial agents [1][2][3][4][5]. The occurrence of 1,2,4-triazole system in numerous biologically active molecules has been recognized to possess activities, such as analgesic [6], antibacterial [7][8][9], antifungal [10,11], anti-inflammatory [12], antitumor [13,14], antitrypanosomal [15], antiproliferative [16] and antibiotics properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…Methoxy-benzoic acid N'[2-(1,5-diethyl-1H-[1,2,4]triazole-3-yl)-acetyl]-hydrazide (8f): Color: Brown crystals. Yield: 80 %.…”
mentioning
confidence: 99%
“…An Indian research team (2012) designed and synthesized novel ofloxacin analogues 13 ( Figure 6 ) as antimicrobial agents. It was observed that 1,2,4-triazole derivatives of ofloxacin with MIC values ranging from 0.25 to 1 µg/mL had antibacterial properties against all tested Gram-positive ( S. aureus , S. epidermis , B. subtilis ) and one Gram-negative ( E. coli ) pathogens, which were comparable to ofloxacin (MICs: 0.25–1 µg/mL) [ 30 ].…”
Section: Antibacterial Activity Of Derivatives Of 124-triazolementioning
confidence: 99%
“…The SAR suggested that the hybrids bearing electron‐withdrawing groups at para ‐position in benzene ring favored the activity while electron‐donating groups were disfavored. Several 1,3,4‐oxadiazole‐5‐thione‐LVFX and 4‐amino‐1,2,4‐triazole‐3‐thione‐LVFX conjugates were examined for their in vitro activities against various pathogens, and most of them were as potent as or better than the parent LVFX against the tested Gram‐negative bacteria .…”
Section: Structure–activity Relationshipmentioning
confidence: 99%